Positioning Strategy Design of Online Travel Agent Applications Based on Perceptual Mapping - Fadhil Muhammad Rafif; Sari Wulandari; Boby Hera Sagita (International Journal of Innovation in Enterprise System, 2022)
Kliktrip is one of the online travel agent application brands with day trip and activity booking services in Indonesia which was established in 2018. In the last few years, Kliktrip has experienced several symptoms, including a decrease in revenue in the second year and the low level of brand differentiation of the Kliktrip online travel agent application based on customer perception compared to other online travel agent application brands. Based on the symptoms of these problems, it can be concluded that the brand of the Kliktrip online travel agent application is weak in customer perceptions of the online travel agent application because customers tend not to know the advantages offered by the Kliktrip online travel agent application brand. To be successful in facing competition with other business competitors, it is necessary to carry out sustainable development by building competitive differentiation by designing and improving positioning strategies. Based on the results of the perceptual mapping, there were 4 groups of competitive areas, the online travel agent Kliktrip application brand was in the same area as the Explorer.id online travel agent application brand which made it the main competitor of the Kliktrip online travel agent application brand. The objectives of this research are to (1) Design a strategy for improving the brand positioning of the online travel agent application and (2) Optimize the resources owned by the Kliktrip online travel agent application brand to implement a strategy for improving the brand positioning of the Kliktrip online travel agent application.